Changing Patterns of Partnering - Weston, R; Qu, L; De Vaus, D (My University, 2003)
There have been important changes over the last 25 years in the way in which men and women form partnered relationships. The authors argue that taking a longer-term perspective provides a better understanding of these trends. Within the last quarter century family structures and relationships have changed in significant ways. One of the most striking changes is in the area of partnering, perhaps the most obvious being the increasing tendency for people to live together without marrying (cohabitation) at some stage in their lives and the fall in first marriage and remarriage rates. This article asks what these trends suggest for the future of marriage. The authors explain that those who focus on the last few decades may well draw markedly different conclusions from those adopt a longer term perspective.
Keywords: Relationships; Families and relationships; Relationships; Families and relationships